The Effect of Financial Indicators on the Gross Domestic Product of the USA Economy for 1990-2015 (A standard study) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Gross domestic product (GDP) is a major indicator of economy for the United States of America, So the federal government tried to maintain its stability by expanding the growth of public spending, tax revenue and public debt, Which means the use of fiscal policy in the management of the overall supply at the level of the modern economy. This study is aimed to estimate and analyze the impact of financial indicators on economic growth based on time series data covering the period 1990-2015 using the VIF and TOL factors and to test the hypotheses and clarifying the relationship between them to verify the validity of the hypothesis.      The obtained results of the analysis of the standard models of the research show there is a positive effect of the financial indicators on US GDP based on the parameter values of the model, As the increase of public expenditure, public revenues and public debt by 1% will increase the GDP by 0.44%, 0.45%, 0.11% respectively. This is compatible with economic logic and theoretical hypotheses.      The study recommends directing public spending and tax revenue as well as public loans towards productive economic areas which supports economic activity and expansion the supply base to cover growing aggregate demand.